2010
DOI: 10.1080/14631370903525645
|View full text |Cite
|
Sign up to set email alerts
|

Individual farm exit decisions in Croatian family farms

Abstract: Successful structural change in agriculture depends on several preconditions, some of which are only indirectly linked to the farming sector. The rural non-farm economy is known as one important driver of structural change because it offers alternative employment. However, little is known about the factors that influence farm exit decisions. Based on a recent household survey of Croatian family farms, we analyse individual employment decisions of farm household members by taking a prospective look at developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In general, research shows that government payments decrease the probability of farm exit and increase farm size. For example, this was found by Goetz and Debertin (2001) for the US farming sector in 1987e1997, Yee and Ahearn (2005) for the US farming sector in 1960e1996, Breustedt and Glauben (2007) for Western Europe between 1993and 1997, Key and Roberts (2007 for the US farming sector between 1978and 1997, and Möllers and Fritzsch (2010 for Croatian farmers in 2007 (from a survey of intentions). The explanation advanced is that subsidies both increase farm profitability (favouring survival) and relax credit constraints (enabling farm expansion).…”
Section: Agricultural Public Policiesmentioning
confidence: 94%
See 2 more Smart Citations
“…In general, research shows that government payments decrease the probability of farm exit and increase farm size. For example, this was found by Goetz and Debertin (2001) for the US farming sector in 1987e1997, Yee and Ahearn (2005) for the US farming sector in 1960e1996, Breustedt and Glauben (2007) for Western Europe between 1993and 1997, Key and Roberts (2007 for the US farming sector between 1978and 1997, and Möllers and Fritzsch (2010 for Croatian farmers in 2007 (from a survey of intentions). The explanation advanced is that subsidies both increase farm profitability (favouring survival) and relax credit constraints (enabling farm expansion).…”
Section: Agricultural Public Policiesmentioning
confidence: 94%
“…Breen et al (2005) observed that farmers' responses to policy changes may not be as strong as expected due to 'individual circumstances' and highlighted the importance of taking into account farm and farmer characteristics. Among these, initial farm size was found to be an important determinant of structural change in the US (Foltz, 2004;Key and Roberts, 2007), in Israel and Canada (Kimhi and Bollman, 1999), and in Europe (Weiss, 1999;Pietola et al, 2003;Glauben et al, 2006;Breustedt and Glauben, 2007;Möllers and Fritzsch, 2010). Studies have generally found that larger farms have a lower probability of leaving farming, due to the higher opportunity costs of quitting and because the household income of such farms is more sustainable.…”
Section: Agricultural Public Policiesmentioning
confidence: 94%
See 1 more Smart Citation
“…As evidenced in the study of Roseman (2013), which examined the effect of youth unemployment on rural development in Galicia, youth unemployment in particular is one of the most serious issues, and so it is important to seek instruments to help reducing unemployment in rural areas. The considerable problem with unemployment particularly among young people has also been studied by Möllers and Fritzsch (2010) in Croatia, where they found evidence that despite a considerable interest among young people to start farming, they frequently face problems due to the insufficient education, the lack of farm family traditions, and problematic approaches to access the land.…”
Section: Situation In the Czech Republicmentioning
confidence: 99%
“…It was found that the exit hazard rates are significantly different among the states studied because of the farm size that mostly describes these states heterogeneity. Möllers and Fritzsch (2010) investigated the factors determining farm exits on the base of the Croatian family farms. The authors found that mixed activities and the part-time farming are at the core of the expected future farm developments.…”
Section: Farm Exitingmentioning
confidence: 99%